Analysis of User Satisfaction with the Academic Information System (SIMAK) Using the End-User Computing Satisfaction (EUCS) Method: A Case Study at Universitas Muhammadiyah Palembang - Abi Ramadhan (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2023)
The Academic Information System (SIMAK) was designed to manage academic data and schedules to facilitate user access and convenience in campus academic activities. Since its implementation at Universitas Muhammadiyah Palembang (UMP) in 2016, SIMAK has supported key academic functions such as course registration (KRS), grade viewing (KHS), and other academic processes. However, a formal evaluation of end-user satisfaction with SIMAK has not yet been conducted. This study aims to determine the level of user satisfaction and identify the factors influencing student perceptions of SIMAK’s performance. The research employs a quantitative approach based on the End-User Computing Satisfaction (EUCS) model. The population consists of 8,796 active students at UMP, from which 383 respondents were selected using the Slovin formula. Data were collected through an online questionnaire distributed via Google Forms and analyzed using SPSS version 25, including validity, reliability, and hypothesis testing. The results show a positive and significant simultaneous effect of the variables content, format, and timeliness on user satisfaction, with Fcount (287.179) > Ftable (2.2378) and a significance value of 0.000 < 0.1.